Comparison of Epidural Steroid Injections with Conservative Management in Patients with Lumbar Radiculopathy - Rahman, Md Mahmudur; Rashid, Md Imamur; Rahman, Nadia; Shakoor, MA (Medicine Today, 2014)
Pain in the back is the most common of all chronic pain disorders. Back pain and sciatica, or leg pain originating from injury to or pressure on the sciatic nerve, are major causes of disability in adults, occurring in 15% to 20% of the working-age population annually and 70% to 90% of adults at some point in their lives. Men and women are affected equally. The study was conducted prospectively in 60 patients of 18 to 60 years of age with documented chronic low back pain with sciatica. Thirty patients were treated in group-A with conservative treatment (NSAID+ therapeutic exercises+ superficial thermotherapy and ADL instruction) plus epidural steroid injection and 30 samples were treated in group B with conservative treatment only. Epidural steroid injection treatment group is significantly improved than conservative treatment group (p<0.05). There was more improvement of pain in group A than in Group B ( p= 0.007) and SLR was more increased in group A than group-B (p=0.03). So, epidural steroid injection is a effective treatment for lumber rediculopathy especially in acute phase. DOI: http://dx.doi.org/10.3329/medtoday.v26i1.21302 Medicine Today 2014 Vol.26(1): 09-11